The figure is made up of two semi-circles and one triangle
--------------------------------
Find Radius
--------------------------------
Radius = Diameter ÷ 2
Radius = 5 ÷ 2
Radius = 2.5 ft
Area of the semi-circle = 1/2 πr²
Area of the semi-circle = 1/2 x π x (2.5)²
Area of the semi-circle = 9.82 ft²
Area of the triangle= 1/2 x base x height
Area of the triangle = 1/2 x 6 x 4
Area of the triangle = 12 ft²
Total area = 9.82 + 9.82 + 12
Total area = 31.63 ft²
--------------------------------------------
Total Area = 31.63 ft²
--------------------------------------------
Answer:
4
Step-by-step explanation:
Fernando-
Child 1- Child 2-
2 kids- 2 kids- = 4 grandchildren for Fernando
2 kids 2 kids These are his great grandchildren, not grandchildren.
Answer:
66 2/3 %
Step-by-step explanation:
First find the students not in the 8th grade
24 - 8 = 16
16 students are not in the 8th grade
Take the fraction of the students not in the 8th grade over the total
16/24 = 2/3
Change to a decimal
.66666666666
Multiply by 100 to change to a percent
66.666666%
66 2/3 %
Answer:
c
Step-by-step explanation:
i think c but not sure
Answer:
Tn = 2Tn-1 - Tn-2
Step-by-step explanation:
Before we can generate the recursive sequence, we need to find the nth term of the given sequence.
nth term of an AP is given as:
Tn = a+(n-1)d
If a17 = -40
T17 = a+(17-1)d = -40
a+16d = -40 ...(1)
If a28 = -73
T28 = a+(28-1)d = -73
a+27d = -73 ...(2)
Solving both equations simultaneously using elimination method.
Subtracting 1 from 2 we have:
27d - 16d = -73-(-40)
11d = -73+40
11d = -33
d = -3
Substituting d = -3 into 1
a+16(-3) = -40
a - 48 = -40
a = -40+48
a = 8
Given a = 8, d = -3, the nth term of the sequence will be
Tn = 8+(n-1) (-3)
Tn = 8+(-3n+3)
Tn = 8-3n+3
Tn = 11-3n
Given Tn = 11-3n and d = -3
Tn-1 = Tn - d... (3)
Tn-1 = 11-3n +3
Tn-1 = 14-3n
Tn-2 = Tn-2d...(4)
Tn-2 = 11-3n-2(-3)
Tn-2 = 11-3n+6
Tn-2 = 17-3n
From 3, d = Tn - Tn-1
From 4, d = (Tn - Tn-2)/2
Equating both common difference
(Tn - Tn-2)/2 = Tn - Tn-1
Tn - Tn-2 = 2(Tn - Tn-1)
Tn - Tn-2 = 2Tn-2Tn-1
2Tn-Tn = 2Tn-1 - Tn-2
Tn = 2Tn-1 - Tn-2
The recursive formula will be
Tn = 2Tn-1 - Tn-2